2022
DOI: 10.31234/osf.io/vjasg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence, Age of Decision, and Interpersonal Warmth Judgements of Childfree Adults: Replication and Extensions

Abstract: Childfree individuals, who are also described as "childless by choice" or "voluntarily childless", have decided they do not want biological or adopted children. This is an important population to understand because its members have unique reproductive health and end-of-life needs, and they encounter challenges managing work-life balance and with stereotypes. Prior estimates of childfree adults' prevalence in the United States, their age of decision, and interpersonal warmth judgements have varied widely over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 29 publications
2
18
2
Order By: Relevance
“…Following J. W. Neal and Neal (2023a), we identify childfree respondents as those who answer “no” to each of the following questions: (1) “Do you have, or have you ever had, any biological, step-, or adopted children,” (2) “Do you plan to have any biological or adopted children in the future,” and (3) “Do you wish you had or could have biological or adopted children.” All other respondents are classified as not childfree.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following J. W. Neal and Neal (2023a), we identify childfree respondents as those who answer “no” to each of the following questions: (1) “Do you have, or have you ever had, any biological, step-, or adopted children,” (2) “Do you plan to have any biological or adopted children in the future,” and (3) “Do you wish you had or could have biological or adopted children.” All other respondents are classified as not childfree.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding stereotypes about childfree adults is important for two reasons. First, recent estimates find that childfree adults may comprise over a fifth of the adult population (J. W. Neal & Neal, 2023a), suggesting that these stereotypes may affect a substantial number of people. Second, stereotypes may lead childfree adults to experience discrimination in the workplace and other social settings (Turnbull et al, 2016;Verniers, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them make these decisions regarding their procreative intentions in their childhood or adolescence. Approximately two-thirds of them decide this before reaching the age of 30, with up to 30% deciding in their thirties and forties (Avison & Furnham, 2015;Ciesielski & Bakiera, 2023;Neal & Neal, 2022;Watling Neal & Neal, 2023). People do not want to have children for a variety of reasons, among which are: those concentrated on developing their own "self" (e.g., they want to pursue their career; they are not interested in raising a child; they want to be free from limitations connected with raising a child); those concentrated on the wellbeing of the potential child (e.g., they are aware of climate change and overpopulation; they believe that having a child in a dangerous world is immoral; or they think that they would be a bad parent and therefore want to avoid hurting their potential child) (Avison & Furnham, 2015;Ciesielski & Bakiera, 2023).…”
Section: Childfreenessmentioning
confidence: 99%
“…For example, some studies restrict their universe to only women [ 2 ], only men [ 5 ], or only ever-married or partnered adults [ 4 ]. These restrictions in the gender or martial status of respondents may lead to variations in estimated prevalence because, for example, some studies have found that more men are childfree than women [ 6 , 12 ], or that more singles are childfree than ever-married or partnered individuals [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%